Pengaruh Gaya Kepemimpinan Dan Motivasi Terhadap Kinerja Aparatur Pada Kantor Desa Madobag Kecamatan Siberut Selatan Kabupaten Kepulauan Mentawai - Sutiyem Sutiyem; Jumiatul Mulya; Dessy Trismiyanti; Jusmanto Samalelet (JURNAL PUNDI, 2023)
This research aims to determine how much influence leadership style and motivation have on the performance of apparatus at the Madobag Village Office, South Siberut District, Mentawai Islands Regency. The type of research used is quantitative research methods. The number of samples in this study was 35 people. The analytical method used is Multiple Linear Regression Analysis. The results of the research show that leadership style has a positive and significant effect on the performance of apparatus at the Madobag Village office, South Siberut District, Mentawai Islands Regency. Motivation has a positive and significant effect on the performance of apparatus at the Madobag Village Office, South Siberut District, Mentawai Islands Regency. Based on the F test, leadership style and motivation simultaneously influence the performance of apparatus at the Madobag Village Office, South Siberut District, Mentawai Islands Regency. The R Square value is 0.989% which means that Leadership Style and Motivation are able to influence the Performance of Apparatus at the Madobag Village Office, South Siberut District, Mentawai Islands Regency by 98.9%, the remaining 0.11% is influenced by other factors not examined in this research. Keywords: Apparatus Performance, Leadership Style, Motivation